The Bull, the Cave and the Angel: A Widely Circulating Hagiographical Text (BHL 5948) - Lagioia, Alessandro (2024)
This article aims to reconsider some previous explanations, and to propose new reflections on the genesis and function of the hagiographical text known as the Apparitio Sancti Michaelis in Monte Gargano. After a brief consideration of the narrative’s environmental setting, the sections of the legend are presented and analysed. The analysis focuses on selected topics: the hagiographer’s intention to convey the idea of a cultic substitution in the Gargano, the hagiographical topos of the animal uncovering the divinity, and the symbolic value of the characters involved. The date of the work’s composition, its intent, and issues of authorship are therefore examined.
Keywords: Christianisation; Hagiography; Mount Gargano; St. Michael the Archangel